New Visions in Plant Science 2018
DOI: 10.5772/intechopen.76590
|View full text |Cite
|
Sign up to set email alerts
|

Risks, Uncertainties, and Ethics of Nanotechnology in Agriculture

Abstract: The use of agrochemicals, though has increased the agricultural productivity, has severely adversely affected soil and aquatic systems with associated flora and fauna and also the health of the farmers and society consuming the chemically grown food. Therefore, the advent of nano-agrochemicals, such as nanopesticides, nanofertilizers and nanosensors, designed to increase solubility, enhances bioavailability and promotes targeted delivery, and their controlled release will have immense potential benefits that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…[ 44 ] However, concern about potential negative public reception surrounding the introduction of nanomaterials into the food chain is a significant limiting factor for the future use of engineered nanomaterials in agriculture. [ 45 ] For example, when plants are exposed to carbon nanotubes (CNT) through their roots or leaves, the applied nanomaterials can spread throughout the whole plant and reach reproductive tissues such as seeds and fruits, [ 46 ] contaminating edible parts. [ 47 ] CNTs have been a popular choice of nanocarrier for the delivery of biomolecules into plant cells due to their penetrative ability, which is in part due to their high aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 ] However, concern about potential negative public reception surrounding the introduction of nanomaterials into the food chain is a significant limiting factor for the future use of engineered nanomaterials in agriculture. [ 45 ] For example, when plants are exposed to carbon nanotubes (CNT) through their roots or leaves, the applied nanomaterials can spread throughout the whole plant and reach reproductive tissues such as seeds and fruits, [ 46 ] contaminating edible parts. [ 47 ] CNTs have been a popular choice of nanocarrier for the delivery of biomolecules into plant cells due to their penetrative ability, which is in part due to their high aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Due on their size and physicochemical properties, it is possible to cross the cell wall and bioaccumulation of nano particles when compared to larger molecules of the same material. Literature shows that nanoparticles especially engineered nano particles have both chronic and acute toxicological effect (Mwaanga, 2018). For example silver nano particles have several applications in agriculture and it is reported that these silver nanoparticles have several toxic effects such as mitochondrial dysfunction due to change in cell permeability for K + and Na + ions (Kone et al, 1988); induce pronounced toxic effects on the proliferation and cytokine expression of peripheral blood mononuclear cells (PBMCs), as reported by Shin et al (2007), and toxic effects on the male reproductive system, as indicated by McAuliffe et al (2007).…”
Section: Potential Threats Related To Nano Agrochemicalsmentioning
confidence: 99%